Small protein sequences can induce cellular uptake of complex nanohybrids - Jan-Philip Merkl; Malak Safi; Christian Schmidtke; Fadi Aldeek; Johannes Ostermann; Tatiana Domitrovic; Sebastian Gärtner; John E. Johnson; Horst Weller; Hedi Mattoussi (Beilstein Journal of Nanotechnology, 2019)
In this letter, we report on the ability of functional fusion proteins presenting a lytic gamma peptide, to promote interactions with HeLa cells and delivery of large hybrid nanostructures.